Students' Perspective on the Interim Government of Bangladesh: A Study at the University of Rajshahi - Hossan, Md. Alomgir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Purpose. This study investigates the perceptions, expectations, and attitudes of students at Rajshahi University regarding the interim government in Bangladesh, which emerged during a critical phase of democratic transition. The interim government's primary role is to implement essential reforms and ensure the transfer of power to a democratically elected political government through fair and timely elections. Design/Methodology/Approach. A mixed-method approach was adopted, combining both qualitative and quantitative data collection techniques. Structured printed questionnaires were distributed among Rajshahi University students, incorporating both closed-ended and open-ended questions. The closed-ended questions provided measurable data, while the open-ended section allowed respondents to freely express their views. Microsoft Excel was used for data analysis and graphical representation, and Microsoft Word was used for drafting the report. Findings. The results indicate that the majority of students at Rajshahi University hold a generally positive view of the interim government. Most respondents support the idea of essential reforms before the transition to an elected government. However, there is a divergence of opinion regarding the duration of the interim government's tenure. While some students advocate for an extended reform period, others emphasize the urgency of restoring a political government through prompt elections. This division reflects the broader societal debate surrounding the balance between stability and democratic continuity. Originality/Value. This research contributes original insights into youth perspectives on governance and democratic transitions in Bangladesh. It highlights the role of educated youth as active stakeholders in political discourse and offers valuable data that can inform future policy decisions during transitional political phases. By focusing on Rajshahi University students, the study provides a focused but significant window into how Bangladesh’s younger generation interprets and engages with periods of political transformation.